2015
DOI: 10.1111/inr.12195
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' extended work hours: Patient, nurse and organizational outcomes

Abstract: Our findings add to increasing international evidence that nurses' poor working conditions result in negative outcomes for professionals, patients and health systems. Policymakers need to be aware of the issues regarding nurses' extended work hours, which has been found to contribute to burnout. Urgently, nurse and health administrators need to develop and implement appropriate nursing overtime policies and strategies to help reduce this phenomenon, including measures to overcome the nursing shortage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 20 publications
3
80
0
6
Order By: Relevance
“…[5] However, more recent studies have found reduced roster flexibility, increased fatigue and burnout. [77][78][79] Risks to nurse welfare due to longer shifts may also be compounded by increased paid overtime which was worked 22% more hotfloor nurses. [76] Furthermore, hot-floor operational flexibility increases patient volume per bed and subsequent workload, which when combined with a technically complex and emotionally demanding work environment, may increase nurse fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…[5] However, more recent studies have found reduced roster flexibility, increased fatigue and burnout. [77][78][79] Risks to nurse welfare due to longer shifts may also be compounded by increased paid overtime which was worked 22% more hotfloor nurses. [76] Furthermore, hot-floor operational flexibility increases patient volume per bed and subsequent workload, which when combined with a technically complex and emotionally demanding work environment, may increase nurse fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…O ritmo de trabalho dos trabalhadores de enfermagem também é destaque nas produções científicas (19,31,33,37) , assim como a carga horária excessiva de trabalho exercida pelos trabalhadores (15,17,19,(27)(28)32,34,39,(42)(43) , dimensionamento inadequado (55)(56) , dificuldade nas relações interpessoais (55) , e estes são considerados fatores determinantes da carga psíquica.…”
Section: Categoria 2 -Condições De Trabalho Que Predispõem àS Cargas unclassified
“…Outras consequências estão voltadas ao desgaste emocional (11,16,23,27,33,36,39,49) , associado à ocorrência de acidentes e problemas de saúde (11) , preocupação, perda de sono, ansiedade, medo, descontrole emocional, problemas no relacionamento com a família (24) , desgaste físico e emocional (27,29,56) . A falha de memória, dificuldade de concentração, medo de cometer erros (13) , e perturbações do sono (13,(37)(38) também são influências das cargas de trabalho na saúde do trabalhador.…”
Section: Categoria 3 -Influências Das Cargas De Trabalho Na Saúde Do unclassified
See 1 more Smart Citation
“…Burnout is also characterized by emotional exhaustion, depersonalization, and reduced personal completion (6)(7)(8). On the other hand, one context contrary to burnout is that human beings believe that life is full of meaning; therefore, they need and look for meaningful action in their work (9).…”
Section: Introductionmentioning
confidence: 99%